Chemical composition of rainwater during monsoon season over Pune (Maharashtra) and its relation to meteorological factors (MAUSAM, 1985)
About 180 rainwater samples were collected at Pune during the monsoon season of 1981 and analysed for various chemical constituents. Data have been utilised to study the importance of various contributing sources to the composition of rainwater, role of cations and anions in controlling the pH of rainwater and the influence of meteorological parameters on the chemical composition.It has been found that maritime air is the major source of CI and Na and for SO, anthropogenic sources appear to be quite important. In addition to above, local soil also contributes to the concentration of constituents, specially to cations and the samples get enriched to a large extent in terms of Ca, SO and K. pH values remained in basic range and H+ ions were significantly correlated with excess SO. (positive) and Ca (negative). Negative correlation between excess Ca and H+ ions indicates the importance of dissolution and exchange reaction involving particulate material (calcareous minerals) thereby which H+ ions are consumed. Concentration of NH. have been found to depend on soil temperature and SO4 correlated well with the R. H. in the atmosphere. Studies also indicate that nitrate concentrations are higher in rainwater samples associated with thunderstorms in comparison to the samples not associated with thunderstorm.